Assessing Student Independence for Effective Learning via Digital Modules in Economics - Friyatmi; Tuti Kamila Sukma; Socheath Mam (International Journal of Education and Teaching Zone, 2025)
Due to Generation Z's lack of learning autonomy and limited digital learning resources, the utilization of digital modules that consider students' needs is critical. This study aimed to examine student independence in economics learning that integrates digital modules. An experimental design with a posttest-only control group was applied, comparing students who used digital modules with those who relied on printed modules. Treatment effects were assessed using an independent sample t-test. The results show that digital modules significantly enhanced students’ independence. This finding suggests that digital modules are not only effective in strengthening 21st-century learning competencies but also provide practical guidance for educators in designing more learner-centered instructional materials. Moreover, the results provide helpful ideas for policymakers in promoting the digitalization of curriculum resources to support student independence and educational quality improvement.